Legal Implications of Land Ownership Rights of Dago Elos Residents Following the Decision No. 601/Pid.B/2024/PN Bdg - Prawira, Muhammad Syeisar Nanda; Suhariningsih Suhariningsih; Herlindah Herlindah (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
This study examines the legal implications of land ownership rights in Dago Elos following Bandung District Court Decision No. 601/Pid.B/2024/PN Bdg, which annulled the inheritance claim by the Muller Family over land formerly titled as Eigendom Verponding Nos. 3740, 3741, and 3742. Previously, the Supreme Court Decision No. 109 PK/Pdt/2022 had ruled in favor of the Muller Family and ordered Dago Elos residents to vacate the land they had occupied for decades. However, in 2024, new legal evidence (novum) emerged proving the Muller Family committed inheritance fraud, as confirmed by a criminal verdict. This research adopts a normative juridical method with a case and statutory approach. The findings reveal that falsified heirship documents invalidate the Muller Family’s legal standing over the disputed land. Under Supreme Court Circular No. 10 of 2009, the affected residents have the right to submit a second judicial review to restore their land rights. This study highlights the importance of substantive justice in agrarian disputes and the necessity of legal protection for communities with long-standing physical control over their land.